The Role of Renin-Angiotensin-Aldosterone System in the Heart and Lung: Focus on COVID-19 - Mascolo, Annamaria; Scavone, Cristina; Rafaniello, Concetta; De Angelis, Antonella; Urbanek, Konrad; di Mauro, Gabriella; Cappetta, Donato; Berrino, Liberato; Rossi, Francesco; Capuano, Annalisa (Frontiers in Pharmacology, 2021)
The renin-angiotensin-aldosterone system (RAAS) firstly considered as a cardiovascular circulating hormonal system, it is now accepted as a local tissue system that works synergistically or independently with the circulating one. Evidence states that tissue RAAS locally generates mediators with regulatory homeostatic functions, thus contributing, at some extent, to organ dysfunction or disease. Specifically, RAAS can be divided into the traditional RAAS pathway (or classic RAAS) mediated by angiotensin II (AII), and the non-classic RAAS pathway mediated by angiotensin 1-7. Both pathways operate in the heart and lung. In the heart, the classic RAAS plays a role in both hemodynamics and tissue remodeling associated with cardiomyocyte and endothelial dysfunction, leading to progressive functional impairment. Moreover, the local classic RAAS may predispose the onset of atrial fibrillation through different biological mechanisms involving inflammation, accumulation of epicardial adipose tissue, and electrical cardiac remodeling. In the lung, the classic RAAS regulates cell proliferation, immune-inflammatory response, hypoxia, and angiogenesis, contributing to lung injury and different pulmonary diseases (including COVID-19). Instead, the local non-classic RAAS counteracts the classic RAAS effects exerting a protective action on both heart and lung. Moreover, the non-classic RAAS, through the angiotensin-converting enzyme 2 (ACE2), mediates the entry of the etiological agent of COVID-19 (SARS-CoV-2) into cells. This may cause a reduction in ACE2 and an imbalance between angiotensins in favor of AII that may be responsible for the lung and heart damage. Drugs blocking the classic RAAS (angiotensin-converting enzyme inhibitors and angiotensin receptor blockers) are well known to exert a cardiovascular benefit. They are recently under evaluation for COVID-19 for their ability to block AII-induced lung injury altogether with drugs stimulating the non-classic RAAS. Herein, we discuss the available evidence on the role of RAAS in the heart and lung, summarizing all clinical data related to the use of drugs acting either by blocking the classic RAAS or stimulating the non-classic RAAS.